2020
DOI: 10.1039/d0ra01442g
|View full text |Cite
|
Sign up to set email alerts
|

Continuous flow synthesis of phase transition-resistant titania microparticles with tunable morphologies

Abstract: A flow chemistry strategy for synthesis of anatase titania microparticles utilizing a flow-focusing microreactor integrated with a collimated UV LED is presented. The synthesized microparticles possess a wide variety of morphologies and high surface areas (up to 362 m2 g−1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Flow Synthesis Procedure . Droplets of the appropriate precursor mixture were formed using the axisymmetric flow focusing device using the previously reported procedure [21,23] . Briefly, after droplet formation, the ETPTA present in the precursor was polymerized in operando using a collimated UV LED (365 nm, ThorLabs M365LP1 C), after which the photocrosslinked particles were collected in a vial containing pure formamide.…”
Section: Methodsmentioning
confidence: 99%
“…Flow Synthesis Procedure . Droplets of the appropriate precursor mixture were formed using the axisymmetric flow focusing device using the previously reported procedure [21,23] . Briefly, after droplet formation, the ETPTA present in the precursor was polymerized in operando using a collimated UV LED (365 nm, ThorLabs M365LP1 C), after which the photocrosslinked particles were collected in a vial containing pure formamide.…”
Section: Methodsmentioning
confidence: 99%
“…Nitrogen (N 2 , grade 5.0) and CO 2 (industrial-grade) were purchased from Messer. The graphite-titania (G-TiO 2 composite) microspheres used to pack the flow reactor were synthesized using a flow-focusing microreactor presented previously by our group. However, rather than annealing the microparticles at 500 °C, the in-flow synthesized microparticles were calcined under ambient atmosphere at 400 °C, which resulted in the formation of G-TiO 2 composite microparticles. Deionized (DI) water (18 MΩ-cm) was generated using the on-site facility.…”
Section: Methodsmentioning
confidence: 99%
“…The second category, tube or capillary-based microreactors ( Figure 2B), are commonly constructed from inexpensive, commercially-available components such as metal or polymer tubing, [64] glass capillaries, [65,66] and needles, with little, if any, modification. The use of these materials often enables facile (off-the-shelf) microreactor construction at a fraction of the time and cost associated with microfabricated reactor assembly.…”
Section: Types Of Microscale Flow Chemistry Platformsmentioning
confidence: 99%
“…It was found that the resulting microspheres possessed surface areas up to 259 m 2 g -1 and resisted phase transition to the rutile phase even at temperatures up to 800 °C ( Figure 4D). Following the development of a hybrid hydrolytic-oxidative process for TiO 2 synthesis, Campbell et al [66] combined the reported flowfocusing microreactor using a formamide continuous phase with in situ UV crosslinking to intensify the synthetic process and almost fully eliminate hydrolysis ( Figure 4E). The integration of a collimated UV LED (385 nm) with the microreactor enabled the use of TBT concentrations ranging from 12-50 wt% TBT and synthesis of a wide variety of morphologies including hollow, yolk-shell, thick shell, macroporous, and dense microspheres.…”
Section: Metal Oxide Microparticlesmentioning
confidence: 99%
See 1 more Smart Citation